FAKTOR YANG MEMPENGARUHI NON-PERFORMING LOAN PADA BANK PEMERINTAH DAN BANK ASING DI INDONESIA - Rahimah, Evida; Pratidina Nasution, Siti Wardah; Arfah Nasution, Siti Ummi (Jurnal Manajemen Akuntansi (JUMSI), 2021)
The purpose of this research to know and analyze effect of Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), Net Interest Margin (NIM), Earning Assets Quality Ratio (KAP), Operations Expenses to Operations Income (BOPO), Bank Size, Return on Equity (ROE), Gross Domestic Product (GDP) and inflation to the Non-Performing Loan (NPL) government and foreign banks in Indonesia and Comparison effect of Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), Net interest Margin (NIM), Earning Assets Quality Ratio (KAP), Operations Expenses to Operations Income (BOPO), Bank Size, Return on Equity (ROE) to the Non-Performing Loan (NPL) government and foreign banks in Indonesia. This research used 8 samples are 4 government banks and 4 foreign banks in Indonesia as an object of research, the research period is from year 2006 until 2013. Data used in this research was obtained from the Financial Statements of government and foreign banks. This research used a significance level of 5%. In analyzing data, researcher used independent sample t-test, while the test of hypothesis is leven's test, free sample t test and significance test. Panel data regression is estimate panel data model, and then f test, t test and coefficient test of determination. The result showed that there is difference between CAR, LDR, NIM, Bank Size, ROE and no difference between KAP, BOPO and NPL government and foreign banks in Indonesia. CAR, LDR, NIM, KAP, BOPO, Bank Size, ROE, GDP and inflation simultaneously have a positive effect and significant to NPL government and foreign banks in Indonesia. Partial test result show that Â CAR, NIM, BOPO, ROE and inflation have a negative effect and not significant, LDR and GDP have positive effect and not significant, KAP have positive effect and significant, SIZE have negative effect and significant to NPL government and foreign banks in Indonesia.